An Evaluation of Antibiotic Prescribing Practices in a Rural Refugee Settlement District in Uganda - Matua Bonniface; Winnie Nambatya; Kalidi Rajab (MDPI AG, 2021)
Ensuring access to effective antibiotics and rational prescribing of antibiotics are critical in reducing antibiotic resistance. In this study, we evaluated antibiotic prescribing practices in a rural district in Uganda. It was a cross-sectional study that involved a retrospective review of 500 outpatient prescriptions from five health facilities. The prescriptions were systematically sampled. World Health Organization core medicine use prescribing and facility indicators were used. Percentage of encounters with one or more antibiotics prescribed was 23% (10,402/45,160). The mean number of antibiotics per prescription was 1.3 (669/500). About 27% (133/500) of the diagnoses and 42% (155/367) of the prescriptions were noncompliant with the national treatment guidelines. Prescribing antibiotics for nonbacterial infections such as malaria 32% (50/156) and noninfectious conditions such as dysmenorrhea and lumbago 15% (23/156) and nonspecific diagnosis such as respiratory tract infection 40% (59/133) were considered noncompliant with the guidelines. On average, 68% (51/75) of the antibiotics were available on the day of the visit. Inappropriate prescribing practices included excessive use of antibiotics and failure to diagnose and prescribe in compliance with treatment guidelines. There is a need to strengthen antibiotic use in the health facilities through setting up stewardship programs and interventions to promote adherence to national treatment guidelines.